RESTORING THE PAST: INVESTIGATING BIREUEN PENDOPO’S PRE-INDEPENDENCE TO PRESENT JOURNEY - Najoan, S. J; Mandey , J (Advanced Journal of Environmental Sciences (AJES), 2023)
Indonesia boasts a rich heritage of historical buildings dating back to the Dutch colonial era, comprising diverse structures such as government buildings, hospitals, houses, tombs, monuments, schools, stations, factories, and airports. While some of these buildings remain intact, others have suffered damage or been lost over time. Among the preserved architectural wonders, the pendopo stands out, serving as office spaces, convention halls, or residences. Aceh Province in Indonesia is home to several such pendopo buildings, six of which remain intact and in use today. Preservation efforts focus on repairing fragile components, repainting, and replacing damaged materials while honoring the original design. Bireuen Regency holds a unique place in history, its architectural influences tracing back to the colonial period. The Dutch government building, now known as the Bireuen Pendopo, has evolved from being a government establishment to serving as the residence of the Bireuen Regent. With ties to President Soekarno, who once used it as his temporary office during a visit, the Regent’s Pendopo is a cultural and historical tourism site estimated to be over 70 years old, according to photo archives dating back to 1948. This research delves into the evolution of the Bireuen Pendopo, analyzing its physical changes over three distinct periods: pre-independence (1934–1944), independence (1945–1998), and after the area expansion (1999–2021). By drawing from limited historical sources, the study aims to shed light on the building’s past and its significance as a protected cultural heritage site. As a testament to the dynamic nature of architecture, the research explores how building functions, construction materials, environmental sustainability, and technological advancements have influenced the pendopo’s transformation over time